In vivo antileishmanial activity of Annona mucosa extracts - Janaína Paolucci Sales de Lima; Maria Lúcia Belém Pinheiro; Ivan Bezerra Allaman; Izaltina Silva-Jardim (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Leishmaniasis, a disease caused by a parasite endemic to large areas of tropical and subtropical countries, is a growing public health problem. METHODS: Male BALB/c mice were infected with Leishmania amazonensis and treated with extracts isolated from Annona mucosa. RESULTS: Treated groups had significantly reduced footpad swelling. The group treated intraperitoneally with hexane extract showed footpad swelling similar to groups treated with Pentamidine® and Glucantime®. Groups treated with dichloromethane extract and hexane extract presented the recovering phenotype associated with reduced parasite levels. CONCLUSIONS: Extracts of A. mucosa are promising sources of novel antileishmanial compounds.